1994
DOI: 10.1007/bf02005756
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of cetirizine on PGE2 release by rat peritoneal macrophages and human monocytes

Abstract: Cetirizine was first described as a specific anti-H1 molecule displaying potent antiallergic activity. It was later found that its pharmacological properties extended to cellular actions as on eosinophil recruitment at inflammatory sites in allergic patients. Monocytes and macrophages participate in allergic mechanisms, particularly through high affinity H1 and H2 membrane receptors and generation of pro- and anti-inflammatory agents; among them histamine-induced factors, IL-1 and prostanoids are of importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Cetirizine a second generation anti-histaminic agent and more specifically an H1 receptor blocker has been observed to reduce PGD2 release from mast cells, 71 whereas, increase the release of PGE2 in a concentrationdependent manner, from human monocytes in in vitro setting. 72 Based on this observations another study designed to evaluate the efficacy of topical 1% cetirizine solution reported significant improvement in hair growth in patients with mild to moderate AGA. 73 In addition, the anti-inflammatory and anti-allergic activities of cetirizine can be useful in AGA patients with scalp irritation and inflammation.…”
Section: Cetirizinementioning
confidence: 90%
See 1 more Smart Citation
“…Cetirizine a second generation anti-histaminic agent and more specifically an H1 receptor blocker has been observed to reduce PGD2 release from mast cells, 71 whereas, increase the release of PGE2 in a concentrationdependent manner, from human monocytes in in vitro setting. 72 Based on this observations another study designed to evaluate the efficacy of topical 1% cetirizine solution reported significant improvement in hair growth in patients with mild to moderate AGA. 73 In addition, the anti-inflammatory and anti-allergic activities of cetirizine can be useful in AGA patients with scalp irritation and inflammation.…”
Section: Cetirizinementioning
confidence: 90%
“…VDR expression has been linked to reduced proliferation and heightened differentiation of keratinocytes which assist in efficient hair cycle progression. 72 Expression of VDR is of more significance for the keratinocyte stem cells located in follicular bulge as any dysfunctionalities in VDR may result in hair cycle progression defects. 74 In fact, the expression of VDR in keratinocytes has been associated with and varies depending on the specific stage of the hair cycle the follicle is in.…”
Section: Vitamin Dmentioning
confidence: 99%
“…The drug has been shown to induce the release of PGE2 from rat peritoneal macrophages and human monocytes [13]; PGE2 exerts a suppressive effect on macrophage functions such as antigen presentation and MHC class II expression [14].…”
Section: Cellular and Humoral Autoimmune Responsesmentioning
confidence: 99%
“…The cells were incubated for 12 h, then cell medium was collected and stored at À 70 -C for analysis. Compound 48/80 (1 Ag/ml) and LPS (10 Ag/ml) were used as positive controls for mediators release (Roch-Arveiller et al, 1994). Mediator concentrations were measured by commercial ELISA kits, with sensitivity at 0.1 pg/ml.…”
Section: Psp-induced Writhing In the Mousementioning
confidence: 99%